Regeneration and Repair in Endodontics-A Special Issue of the Regenerative Endodontics-A New Era in Clinical Endodontics - Tarek Mohamed A. Saoud; Domenico Ricucci; Louis M. Lin; Peter Gaengler (MDPI AG, 2016)
Caries is the most common cause of pulp-periapical disease. When the pulp tissue involved in caries becomes irreversibly inflamed and progresses to necrosis, the treatment option is root canal therapy because the infected or non-infected necrotic pulp tissue in the root canal system is not accessible to the host's innate and adaptive immune defense mechanisms and antimicrobial agents. Therefore, the infected or non-infected necrotic pulp tissue must be removed from the canal space by pulpectomy. As our knowledge in pulp biology advances, the concept of treatment of pulpal and periapical disease also changes. Endodontists have been looking for biologically based treatment procedures, which could promote regeneration or repair of the dentin-pulp complex destroyed by infection or trauma for several decades. After a long, extensive search in in vitro laboratory and in vivo preclinical animal experiments, the dental stem cells capable of regenerating the dentin-pulp complex were discovered. Consequently, the biological concept of 'regenerative endodontics' emerged and has highlighted the paradigm shift in the treatment of immature permanent teeth with necrotic pulps in clinical endodontics. Regenerative endodontics is defined as biologically based procedures designed to physiologically replace damaged tooth structures, including dentin and root structures, as well as the pulp-dentin complex. According to the American Association of Endodontists' Clinical Considerations for a Regenerative Procedure, the primary goal of the regenerative procedure is the elimination of clinical symptoms and the resolution of apical periodontitis. Thickening of canal walls and continued root maturation is the secondary goal. Therefore, the primary goal of regenerative endodontics and traditional non-surgical root canal therapy is the same. The difference between non-surgical root canal therapy and regenerative endodontic therapy is that the disinfected root canals in the former therapy are filled with biocompatible foreign materials and the root canals in the latter therapy are filled with the host's own vital tissue. The purpose of this article is to review the potential of using regenerative endodontic therapy for human immature and mature permanent teeth with necrotic pulps and/or apical periodontitis, teeth with persistent apical periodontitis after root canal therapy, traumatized teeth with external inflammatory root resorption, and avulsed teeth in terms of elimination of clinical symptoms and resolution of apical periodontitis.